Differences in utilization of Intracytoplasmic sperm injection (ICSI) within human services (HHS) regions and metropolitan megaregions in the U.S - Zagadailov, Pavel; Hsu, Albert; Seifer, David B.; Stern, Judy E. (Reproductive biology and endocrinology, 2017)
Anecdotal evidence suggests that US practice patterns for ART differ by geographical region. The purpose of this study was to determine whether use of ICSI differs by region and to evaluate whether these rates are correlated with differences in live birth rates. Public data for 2012 were obtained from the Centers for Disease Control and Prevention. Clinics with ≥100 fresh, non-donor cycles were grouped by 10 nationally recognized Department of Health & Human Services regions and 11 metropolitan Megaregions and were compared for use of ICSI, frequency of male factor infertility, and live birth rate in women <35 years. There were 274 clinics in the Health & Human Services regions and 247 in the Megaregions. ICSI utilization rates in Health & Human Services groups ranged between 52.5-78.2% (P < 0.0001). Live birth rates per cycle in women <35 years differed (34.1-47.6%; P < 0.0001) but did not correlate with rates of ICSI (R = 0.2096; P = 0.18) per cycle. For Megaregions, rates of ICSI per cycle differed (63.4%-93.5%, P < 0.0001) as did live birth rates per cycle for women <35 (36.0%-59.0%, P = 0.001) but there was only minimal correlation between them (R = 0.5347; P = 0.01). Highest rates of ICSI occurred in Front Range (93.5%) and Gulf Coast (83.1%) Megaregions. Lowest rates occurred in the Northeast (63.4%) and Florida (64.8%) Megaregions. Male factor infertility rates did not differ across regions. ICSI utilization and live birth rates per cycle for each clinic group were significantly different across geographical regions of the U.S. However, higher ICSI utilization rate was not associated with higher rates of male factor infertility nor were they strongly correlated with higher live birth rates per cycle. Studies are needed to understand factors that may influence ICSI overutilization in the U.S.